The Correlation Between Students’ Growth Mindset and Students’ GPA Achievement in The English Department of STKIP Yayasan Abdi Pendidikan Payakumbuh - Ridianto, Ridianto; Mahaputri, Dwi Settya; Khoiria, Anisa Uul (Innovative: Journal Of Social Science Research, 2024)
Students who experience difficulties in learning and do not try to solve them will have a low Grade Point Average (GPA). On the other hand, students who attend lectures well will have a high GPA. The aim of this research is to find out whether there is a positive correlation between the development of students' mindsets and their GPA achievement. This research includes all students English class in the STKIP Yayasan Abdi Pendidikan, with a total of 52 students. As tools, this research uses questionnaires and official documents. The data for the official document is a list of students' GPA scores, while the data for the questionnaire is the student answer sheet on the questionnaire about growth mindset. After analyzing the questionnaire with a Likert scale, the researcher used the Spearman rank order formula to analyze the correlation. The results show that rxy is greater than rtable (0.37 > 0.301). Based on the results of the analysis, it can be concluded that there is a moderate positive relationship between students' growth mindset and students' GPA achievement in the English department at STKIP Yayasan Abdi Pendidikan Payakumbuh. This means that a growth mindset has a moderate influence on students' GPA achievement. Keywords: Growth Mindset, Grade Point Average (GPA).